PELATIHAN PEMBUATAN TEH CELUP DARI TANAMAN BUNGA TELANG (Clitoria ternatea) DI SMK PGRI 2 CIMAHI - Haerani, Ani; Ramadhani, Salma Fitria; Putri, Winda Oktapiani; Zahra, Astry Amelia; Anisa, Muthya; Septiardana, Tiara Putri; Gustiawan, Rapli; Alfaridz, Mohamad Rizki; Ramadhani, Salma Fitria Ramadhani (Jurnal Bakti untuk Negeri, 2024)
Tea is a drink that is very common in our daily lives which can be used as a health drink for the body. Tea products are not only made from the tops of tea plant leaves, but can be produced from other leaves such as butterfly pea flowers (Clitoria ternatea). Butterfly pea flowers contain secondary metabolite compounds such as phenols, flavonoids, alkaloids and anthocyanins. These secondary metabolites make telang flowers useful for treating premature aging, cancer, digestive disorders and cardiovascular diseases. The aim of this community service is to introduce tea bags made from butterfly pea flowers. The activity methods used are demonstrations, lectures and discussions. The materials and equipment used are butterfly pea flowers, lemon, warm water, ice cubes, honey and spoons and glasses. Participants who took part in this activity were students of SMK PGRI 2 Cimahi. The results of the training activities that have been carried out are that students at SMK PGRI 2 Cimahi can understand the process of making and using butterfly pea flowers as tea bags and produce healthy tea drinks with flavors that students like. The conclusion of this training is that students can learn about the use of natural ingredients such as butterfly pea flowers as tea bags which have various health benefits.